Geophysical substantiation of reservoir rocks for injecting excess brines from potash production - Trapeznikova , A.B.; Yaroslavtsev, A.G.; Sanfirov, I.A.; Stepanov , Yu.I.; Baibakova , T.V. (Perm Federal Research Centre Journal, 2023)
A range of geophysical research is substantiated in order to identify reservoirs in the interval of the salt and marl formation of the suprasalt complex of the Verkhnekamskoye potash salt deposit for re-injection of waste brines. The choice of injection interval and localization of places for drilling technological wells is justified by comprehensive interpretation of the data of geophysical well surveys, shallow seismic and vertical electrical sounding. Examples of the results of various geophysical methods used to highlight anomalies associated with reservoirs are presented.